THERMAL-MECHANICAL FATIGUE PREDICTION OF ENGINE CYLINDER HEAD BASED ON THE SEHITOGLU MODEL - ZOU PingPing; JING GuoXi; ZENG XiaoChun; LUO XuWei; YUAN XiaoJun; WEI Tao; LIN YuXing (Jixie qiangdu)
The research work was carried out on the mechanical performance testing and characterization of an engine cylinder head material,and the prediction of the cylinder head thermal engine fatigue life. The fluid-solid coupling method was used to obtain accurate results of the thermal boundary and temperature field of the cylinder head. The calculated temperature field is consistent with the measured results. According to the thermal shock test specifications of the whole machine,the Sehitoglu model was used to predict the thermal fatigue life of the cylinder head. The simulation results show that the minimum life of the cylinder head occurs in the nose bridge area on the exhaust side of the second cylinder fire surface,which is mainly caused by environmental damage. The service life is 6 860,which meets the design requirements. At the same time,the cylinder head has successfully passed the heat engine fatigue bench test of the whole machine.